أبعاد الجودة الإلكترونية في مواقع الجامعات السورية على الإنترنت - غدير باسم غدير (Latakia University Journal - Economic and Legal Sciences Series, 2016)
لقد أدّت الثورة العلمية التكنولوجية المعاصرة المتمثّلة بشكل كبير في ثورة الحاسب والإنترنت إلى خلق بيئة عمل جديدة سمّيت ببيئة العمل الإلكترونية(E-Business)، التي بدورها أفرزت مصطلحات جديدة تتناسب وطبيعة تلك البيئة، كمصطلح الجودة الإلكترونية(E-Quality)، الذي يشير إلى تطبيق مختلف مفاهيم الجودة المعروفة في بيئة إلكترونية أساسها الحاسب وشبكاته المختلفة. تتلخّص مشكلة هذا البحث بدراسة تصنيف مواقع الجامعات السورية على الإنترنت، وبدراسة أبعاد الجودة الإلكترونية فيها، والتحديات التي تحول دون رفع مستوى الجودة الإلكترونية لتلك المواقع. بناء عليه يهدف هذا البحثلمعرفة مدى تحقيق مواقع الجامعات السورية لأبعاد الجودة الإلكترونية، من خلال دراسة تطبيقية على مواقع تلك الجامعات، بما يسهم في تطويرها ورفع سويّتها من خلال تحقيقها الفعّال لعناصر الجودة الإلكترونية وأبعادها في بيئة الأعمال الإلكترونية السّورية. يظهر من نتائج هذا البحث وجود ضعف في أبعاد الجودة الإلكترونية لمواقع الجامعات السورية، والتي تتجلّى بضعف تصميم الموقع وانخفاض جودة البرمجية والمعلومات وكذلك ضعف في بُعْد تنوّع الخدمات وبُعْد الأخلاقيات الإلكترونية. The scientific technological contemporary revolution, represented by the Internet and computer technics, has led to a new working environment named E-Business. In turn, this environment has produced some nomenclatures appropriate to its nature such as E-Quality, which refers to the application of various concepts of quality known in computer-based electronic environment and its various networks. This research investigates the problem that discusses the classification of Syrian universities websites, the dimensions of its electronic quality, and the challenges that prevent the lifting of the electronic quality levels in those sites. Accordingly, the aim of this study is to know to which extent Syrian universities websites have adopted the e-quality dimensions. This is done via practical study to the Universities’ websites, in order to achieve an effective development to the Electronic quality elements concept in the E-business environment in Syria. The results of this research showed a weakness in the electronic quality dimensions of the Syrian universities websites, which has been reflected in the weakness of the site design and a decrease in the quality of its software and information, as well as a weakness in the services diversity and electronic ethics.